2016
DOI: 10.1093/ageing/afv204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of orthogeriatric and fracture liaison service models of care for hip fracture patients: population-based longitudinal study

Abstract: Objectives: to evaluate orthogeriatric and nurse-led fracture liaison service (FLS) models of post-hip fracture care in terms of impact on mortality (30 days and 1 year) and second hip fracture (2 years).Setting: Hospital Episode Statistics database linked to Office for National Statistics mortality records for 11 acute hospitals in a region of England.Population: patients aged over 60 years admitted for a primary hip fracture from 2003 to 2013.Methods: each hospital was analysed separately and acted as its ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 28 publications
(38 reference statements)
1
105
1
10
Order By: Relevance
“…There may be an association with the resources available at different times, for example, the provision of orthogeriatrician-led post-hip fracture care has been shown to reduce mortality and this service is not universally available at the weekend [31]. However, in the short/medium term following surgery, the risk of death at the weekend is lower compared to that of weekdays, which suggests care on the ward is likely to be at least equivalent to the care received during the week.…”
Section: Discussionmentioning
confidence: 99%
“…There may be an association with the resources available at different times, for example, the provision of orthogeriatrician-led post-hip fracture care has been shown to reduce mortality and this service is not universally available at the weekend [31]. However, in the short/medium term following surgery, the risk of death at the weekend is lower compared to that of weekdays, which suggests care on the ward is likely to be at least equivalent to the care received during the week.…”
Section: Discussionmentioning
confidence: 99%
“…These models of care reflect the services provided in one regional area in the UK that comprises 11 hospitals receiving patients with acute hip fractures. Details on the OG and FLS models delivered within the region from 2003 to 2013 have been published elsewhere . Briefly, although there was variation across hospitals, the introduction of the OG model involved the appointment of an orthogeriatrician as the clinical lead, responsible for case finding, preoperative assessment, patient assessment, and treatment initiation, as well as having involvement in postoperative care.…”
Section: Methodsmentioning
confidence: 99%
“…Over 2 years of follow-up, a Type A FLS demonstrated a 35% reduction in mortality following a fragility fracture compared with a comparable cohort not assessed by FLS (HR 0.65, 95% CI 0.53–0.79) 41. A large cohort study in the UK using hospital admission data from 11 hospitals also reported a reduction in 30-day mortality by 20% (HR 0.80, 95% CI 0.71–0.91) and 1-year mortality by 16% (HR 0.84, 95% CI 0.77–0.93) in patients admitted to hospital after a hip fracture 44. This data set included hospitals with a newly implemented orthogeriatric service and an FLS program.…”
Section: Fls Outcomesmentioning
confidence: 97%